Isolasi dan Karakterisasi Golongan Senyawa Antibakteri Streptococcus mutans dari Ekstrak Etanol Daun Sosor Bebek (Kalanchoe pinnata (Lamk.) Pers. - NOVI YANTIH; LISIA MARGARET; KARTININGSIH KARTININGSIH (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
Streptococcus mutans is one of the microbes which is responsible for the cause of bad breath. The activity of Kalanchoe pinnata (Lamk.) Pers. leaves ethanol extract is four times stronger than the water extract in inhibiting the growth of Streptococcus mutans. The aim of research is to isolate and characterize an antibacterial compound of ethanol extract of Kalanchoe pinnata (Lamk.) Pers. leaves. The extract was fractionated using column chromatography. The fractions were purified by TLC and the isolate were tested for its purity using HPLC. Isolate was characterized using UV-Vis spectrophotometry and FTIR. Fractionation by column chromatography generated 9 fractions. The fraction VII have the highest diameter of inhibitory against Streptococcus mutans. The yield of isolate was 9.18% of the fraction VII or 0.84% of the ethanol extract with purity of 95%. Isolate was suspected as a group of saponin compound.